Compression ignition and pollutant emissions of large alkylbenzenes. (15th May 2016) - Koivisto, Elina; Ladommatos, Nicos; Gold, Martin
Abstract: This study contributes to combustion research and fuel development by reporting the effect of the phenyl group in alkylbenzenes on combustion characteristics and exhaust gas emissions. The experiments were conducted in a single cylinder compression ignition engine. Three alkylbenzenes with long alkyl chains, three alkane/toluene mixtures and seven alkanes were tested. Additionally, three alcohols were tested to allow comparisons between the effects of a phenyl group and a hydroxyl group. It was found that both the phenyl group and the hydroxyl group have a significant effect on the ignition delay and the exhaust gas emissions. The rate of alkylbenzene combustion was lower than that of the corresponding alkane. Additionally, the phenyl groups in alkane/toluene mixtures had longer ignition delays than the corresponding alkylbenzene molecules. Adding a hydroxyl group to an alkane was observed to increase the ignition delay more than the addition of a phenyl group. It is suggested that these changes in ignition delay are mainly caused by the formation of relatively stable radicals in the combustion of compounds with a phenyl group. The presence of a phenyl group in the fuel molecule also increased the NOx emissions and the mass of particulate emissions in the exhaust gas compared to both alcohols and alkanes.